Teknik Isolasi Antosianin Utama dari Ekstrak Buah Ficus padana Burm.f dengan KCKT Tipe Standar - Syukri, Daimon; Darwir, Djaswir; Santoni, Adlis (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Preparative High Performance liquid chromatography (HPLC) today is one of the popular methods to isolate anthocyanin from extract containing anthocyanins. The working principle of preparative-HPLC can be applied to the laboratory standard tupe of HPLC, so it can be used also to isolate the main anthocyanin compounds from anthocyanin mixtures. The function of fraction collector on preparative HPLC equipment were replaced by opening the mobile phase line after the exit of the detector and hold out the solution manually on the standard type of HPLC. Resolution value between the peaks and the computation time when cuts in the chromatogram peak collection mobile phase containing the analyte is of concern in these activities. The appearace of a single peak in the chromatogram of the isolates showed that the technique can be applied for the simple and fast technique of anthocyanins isolation.Keywords : isolation, anthocyanin, Ficus padana Burm.f, Preparative-HPLC, standar type of HPLC.